1997
DOI: 10.1038/sj.sc.3100394
|View full text |Cite
|
Sign up to set email alerts
|

Densitometric patterns of spinal cord injury associated bone loss

Abstract: The purpose of the study was to use dual energy X-ray absorptiometry to measure bone mineral density (BMD) in the lumbar spine, the femoral neck, Ward's triangle, and the greater trochanter in 204 men (69 able-bodies controls and 135 spinal cord injured patients) strati®ed according to age (20 ± 39, 40 ± 59, and 60+ years old) in order to determine whether changes in BMD were age related, and to determine when these changes began to appear. The BMDs of the lumbar spine of both the 40 ± 59 year old and the 60+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
38
0
7

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 10 publications
6
38
0
7
Order By: Relevance
“…Hip region BMD in our SCI group was 67, 66 and 63% that of the control group, for FN, WT and T, respectively. These ®gures are slightly lower than those found by BeDell et al 21 and Szollar et al, 36 but do support the extent of bone loss at these sites in our SCI individuals.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Hip region BMD in our SCI group was 67, 66 and 63% that of the control group, for FN, WT and T, respectively. These ®gures are slightly lower than those found by BeDell et al 21 and Szollar et al, 36 but do support the extent of bone loss at these sites in our SCI individuals.…”
Section: Discussionsupporting
confidence: 74%
“…35,36 We found no in¯uence of DOI on any bone mass measurement. However our SCI group average for DOI was approximately 10 years, suggesting a plateau at a reduced BMD for the lower limbs and hip region, had been reached.…”
Section: Discussionmentioning
confidence: 61%
“…The patients older than 60 years had a nonsigni®cant increase in the BMD's of the spine and hip regions during this time. 17 We noticed no relation between age and sex of the patients and BMD loss. This may be related to the youth of our patients and the premenopausal status of our female patients.…”
Section: Discussionmentioning
confidence: 63%
“…13 Biering-Sorensen et al 16 showed that BMD of the femoral bone was continuously and signi®cantly decreased in SCI patients aged between 20 ± 55 compared to healthy individuals, while BMD of the lumbar spine was nearly unchanged. Szollar et al 17 showed that during the ®rst year of injury patients between the age of 20 ± 59 displayed a non signi®cant decrease in the BMD's of the spine and the hip regions. The patients older than 60 years had a nonsigni®cant increase in the BMD's of the spine and hip regions during this time.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of normal spine BMD in persons with SCL has been seen in many studies, [1][2][3][16][17][18][19] as opposed to findings in the general older female population and in patients with endocrine disorders, who do lose bone in the spine. 20 In individuals with SCL, however, secondary progressive skeletal abnormalities can lead to significantly increased vertebral bone densitometry results and thereby obscure an underlying osteoporosis.…”
Section: Discussionmentioning
confidence: 93%